Role Of Gandush In The Management Of The Dantharsh (Tooth Sensitivity) - Singour, Ashish Kumar; Mishra, Rajesh; Sahoo, Suchitra (International Research Journal of Ayurveda & Yoga, 2020)
Introduction: In this era due to disturbance of life style and increased amount of the fast food, persons are getting affected with dental problems. Charka has explained the Dantharsh (Dentin hypersensitivity) in the perspective of Gandush method. Aim: The objective of this article is to review the literature of Dantharsh (DH), Dentin hypersensitivity, Gandush (Oil Puling) and its management. Materials and Methods: Article reviewed from the Ayurvedic Text book, journals related to Ayurveda, different search engine, PubMed, Wikipedia and other source material related to this article. Discussion: Gandush is simple and cost effective method as explained in different Samhita. According to Ayurveda Dantharsh is caused by the provocation of Vata Dosh. Sneha used in Gandush is best to pacify Vata Dosh. Sneha strengthens the tissue and increases rich blood supply to periodontal tissue. Conclusion: Gandush with Sesame indicum is effective against pacification of Vata Dosh aggravated in Dantharsh. Sneha Gandush is simple and cost effective method as explained in different Samhita for Dantharsh (Dentin hypersensitivity).